Ammonium cycling in the rocky intertidal: Remineralization, removal, and retention - Santhiska Pather; Catherine A. Pfister; David M. Post; Mark A. Altabet (Limnology and Oceanography, 2014)
Rocky intertidal productivity is traditionally thought to be sustained almost solely by upwelled nitrate with remineralized forms of minor importance. Using tidepools as natural experimental mesocosms, we conducted 15 N‐tracer experiments to test whether ammonium remineralized within the rocky intertidal is also a significant source of fixed N to localized ecosystem production. Comparison of tidepools with and without the dominant bivalve Mytilus californianus allowed consideration of its role in NH + 4 cycling. Closed water‐incubation bottles were used to investigate the contribution of suspended microbes to NH + 4 cycling. Tidepools with mussels had both greater NH + 4 remineralization (two times) and NH + 4 removal as compared with those without, with daytime rates greater than nighttime rates. Incorporation of NH + 4 tracer by particulate organic matter and macroalgae, and the persistence of this signal in tidepools for several days following the experiment, showed retention of autochthonous NH + 4 in the system. Remineralization rates were tightly correlated to removal rates when compared over all treatments and experiments, but NH + 4 remineralization was significantly greater than removal, suggesting a surplus available to nearshore primary producers.